La résistance à venir, pour une autre logique des frontières - Jabre, Elias (Bollettino Filosofico, 2021)
In Resistances ‒ of psychoanalysis, Derrida analyzes through his reading of Freud the repetition compulsion as this irreducible resistance of the unconscious that makes analysis infinite. He introduces the notion of resistance, that comes from this aporetic logic by which psychoanalysis only makes sense to unbind resistances, although it always encounters a non-resistance that resists. He then shows that psychoanalysis maintains a privileged link with the death drive. Through this reading of resistance, psychoanalysis would transform itself and the political field through another formalization of the borders, on the borderline with deconstruction. Keywords: Death Drive, Deconstruction, Psychoanalysis to Come, Repetition Compulsion, Resistance